Characteristic Overview of Drug-Sensitive Pulmonary Tuberculosis Patients with Type 2 Diabetes Comorbidity in Elderly That Visited RSUD R Syamsudin SH Kota Sukabumi from January 2022 to October 2023 - Ramadhan, Muhammad Widad; Afifah, Alidina Nur; Fachri, Muhammad; Farsida, Farsida (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2024)
Background: Tuberculosis (TB) is a global health issue, with over 10 million cases worldwide, and Indonesia ranks as the second-highest country with TB cases. The comorbidity of diabetes mellitus (DM) increases the risk of TB, especially in elderly patients. TB patients with DM are challenging to treat, have low cure rates, and increase the risk of multi-drug resistance TB. Purpose: To understand the characteristic overview of elderly patients with drug-susceptible pulmonary tuberculosis along with type 2 diabetes. Method: This descriptive research utilized surveys with primary data from interviews with elderly patients at RSUD R Syamsudin SH and secondary data from the hospital, covering January 2022 to October 2023. Results: Out of 33 respondents, 20 were male and 13 female. Most (81.8%) had education up to high school, and 72.7% were unemployed. According to BMI, 36.4% had normal weight. Regarding drug adherence, 75.8% supervised it. All respondents had positive chest X-rays for TB, and 87.9% tested positive in molecular rapid tests. Random blood sugar levels showed 12 patients below 200 mg/dl. Among those tested for HbA1c, 78.8% did not undergo the exam, and 6.1% had levels <8%. Conclusion: TB DM predominantly affects elderly males. Most respondents were high school graduates, unemployed, and had normal BMI. They often took on the role of supervising drug adherence. In the Glucose Ad Random, more individuals had levels above 200, and among those tested for HbA1c, many exceeded 7%. All patients showed TB-consistent chest X-rays, with most testing positive in rapid molecular tests.